A comparative study on the dynamics of tensegrity-membrane systems based on multiple models. (15th May 2017) - Yang, Shu; Sultan, Cornel
Abstract: This article investigates the modeling and dynamics of tensegrity-membrane systems. As extensions of tensegrity systems, tensegrity-membrane systems are composed of membranes, bars, and tendons. Significant system complexity and coupling between system components indicate that the behavior of the whole system needs to be investigated. For this purpose a complex nonlinear finite element model is developed to describe system dynamics. Numerical analysis results given by this nonlinear finite element model are compared with the results given by two other models based on different modeling assumptions and of lower complexity. Observations related to key dynamical properties and the influence of modeling assumptions are discussed in detail.